Effect of shading with aluminised screens on fruit production and quality in tomato (Solanum lycopersicum L.) under greenhouse conditions - Callejón-Ferre, A.J.; Manzano-Agugliaro, F.; Díaz-Pérez, M.; Carreño-Ortega, A.; Pérez-Alonso, J. (Spanish Journal of Agricultural Research, 2009)
The purpose of this study was to identify the effects of using aluminised screens offering different degrees of shading on the production and quality of tomato cv Atlético crops grown under greenhouse conditions. The study was performed in an Almería-type "raspa and amagado" commercial greenhouse with an area of 10,000 square m. The covering material was heat-insulating polyethylene (200 microm thick). The passive ventilation area of the greenhouse was 14%. Transplantation of the plantlets into the sandy mulch soil of the greenhouse was performed to leave a density of 1.78 plants/square m. Plants were grown under extendable aluminised screens offering 40% (T40), 50% (T50) and 60% (T60) shading, as well as under traditional whitewashing conditions (control). The screens were used during the middle hours of the day in summer with a view to reducing radiation, and at night in autumn and winter to prevent the loss of heat via outgoing long-wave infrared radiation. Only the T60 treatment returned significantly different results compared to the control: the T60 fruit had a lower deg Brix but were firmer in both growing seasons.